Translation and text types - Dr.Muftah S.lataiwish (مجلة كلية الاداب, 2022)
Abstract Language can function in different occasions; it can establish social relations and express one's mind and personality. The three major types in this paper are descriptive, social, and expressive functions of language. The paper also illustrates text classification The aim of the texts is to convey information. Whether the texts are scientific, technological, commercial, geographical, historical, or philosophical, they are mainly informative.